The Synchronization of Estrous in Sheep and Goats - Hastono, Hastono (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2000)
The review of estrous synchronization was biologically, hormonally, and laserly to studied in the sheep and goat. The observed parameters of the synchronization of estrous in sheep and goat were the onset and the length of estrous. The result of this research shows that the hormonal synchronization of estrous results in the presence of estrous in 30-42 hours after the withdrawal of the sponges; while in goat it is in the average of 35.13±9.9 hours. Than the length of estrous in sheep was 30-48 hours and in goat the average was 36.00±14.96 hours. The synchronization of estrous by Laserpuncture results in the presence of estrous in goat 43.94-59.75 hours after the given laser beam (Animal Production 2(1): 1-8.Key Words: the synchronization of estrous, sheep, goat.